A bio-inspired twin-protuberance hydrofoil design. (15th December 2020) - Kant, R.; Bhattacharyya, A.
Abstract: The hydrodynamic characteristics of a novel twin-protuberance hydrofoil design mimicking the two prominent tubercles present on a humpback whale flipper are investigated. The foil has NACA 634 -021 section with a span/chord ratio of 2, having twin leading-edge protuberances- each of amplitude 10% of the chord length. A characteristic feature of this foil is its capability to restrict the separation zone between the chordwise vortices shed from the two humps at high angles of attack (>20 deg). A detailed comparison study based on experiments and CFD investigations using a transition model is presented for the twin-protuberance hydrofoil with a NACA 634 -021 base foil and a foil with one protuberance of similar configuration. The general observation is a reduced pre-stall lift coefficient and maximum lift for the modified foils along with a higher post-stall lift coefficient compared to the base foil. The influence of Reynolds number and protuberance amplitude and spacing on the hydrodynamic performance is also investigated. The results indicate that such modifications can be used effectively for flow control at high angles of attack and suitably optimized for specific marine applications. Highlights: Novel bio-inspired NACA 634 -021 section hydrofoil with twin leading-edge protuberance. Experiments and CFD investigations using transition model performed. The twin protuberances can restrict the separation domain due to chordwise vortices. Post-stall lift enhancement achieved with modified designs. Influence of Reynolds number and protuberance amplitude investigated.